Phubbing in Social Interaction: A Phenomenological Study on the Urban Young Generation in Pontianak - Zulkarnain; Muhammad Sadikin; Auliya Rochman (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
The rapid advancement of digital technology has significantly changed the pattern of social interaction, especially among urban youth. One form of this transformation is "phubbing". It is a behavior in which individuals ignore others who are physically present because they are too focused on the smartphone. This study aims to understand "phubbing" as a new cultural pattern in the social interaction of urban youth in Pontianak. Using a qualitative phenomenological approach, this study involved ten informants aged 18-25 years who actively used smartphones and had experienced phubbing, both as perpetrators and recipients. The results of the study show that phubbing has become socially normalized and integrated into everyday life, reflecting shifts in social values and norms of interaction. Although it is often considered a routine, phubbing also creates the ambivalence of being accepted and hated. This study shows that phubbing is more than just a digital habit but is also a cultural practice that redefines presence, attention, and social relationships in the digital age.